Ruptured mycotic aneurysm of intercostal arteries associated with vertebral osteomyelitis: a case report - Masatsugu Tsukamoto; Tadatsugu Morimoto; Tomohito Yoshihara; Masaaki Mawatari (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Here, we report a rare case of massive hemothorax caused by rupture of an intercostal artery pseudoaneurysm associated with pyogenic spondylodiscitis, which was successfully treated with endovascular intervention. Case presentation A 49-year-old man with schizophrenia, idiopathic esophageal rupture, postoperative mediastinal abscess, and pyothorax, diagnosed with pyogenic spondylodiscitis caused by methicillin-resistant Staphylococcus aureus. Magnetic resonance imaging and computed tomography (CT) showed extensive vertebral body destruction. The patient underwent a two-stage operation: anterior vertebral debridement and fixation with iliac bone graft and 10 days after first surgery, posterior fixation with instrumentation. Seven days after second surgery, the patient’s right chest pain increased, his blood pressure dropped, and he had shock. Chest X-ray showed massive hemothorax in the right lung. Chest CT and subsequent intercostal arteriography showed a pseudoaneurysm in the right T8 intercostal artery and active contrast extravasation from it. This seemed ruptured mycotic aneurysms involving intercostal vessels. These vessels were successfully embolized using micro-coils. Then, the patient completed the prescribed antimicrobial therapy in the hospital without any complications. Conclusions Intercostal artery aneurysms are rare vascular abnormalities. They have the risk of rupture and may sometimes cause hemothorax and can be potentially life-threatening. Ruptured intercostal artery pseudoaneurysms are a good indication of endovascular intervention, and prompt embolization saved the life of the patient in this case report. This case report highlights the possibility of a ruptured intercostal mycotic aneurysm in patients with pyogenic spondylodiscitis and reminds physicians to be alert of this rare but potentially fatal complication.